Implementation of circuit learning strategies to improve science learning outcomes - Mahyaeny Mahyaeny (Jurnal Pijar Mipa, 2023)
By implementing the Circuit Learning strategy, this research aims to improve student learning outcomes in class VII science subjects at SMPN 4 Mataram in 2022-2023. The type of research used was classroom action research, carried out in two cycles with 32 students. Learning outcome data is collected through evaluation tests, while student activity data is collected through observation sheets. The research results showed that in cycle 1 to cycle 2, the average score was 75 with classical completeness of 72% to an average score of 80 with classical completeness of 87.5%, increasing the average score of results and learning and classical completeness. Meanwhile, the observations of the implementation of the first learning cycle showed that students' learning activities in the learning process were included in the quite active category because the students achieved a score of 3 following the lessons. In cycle II, the score obtained was 4.6, which was included in the active category. It shows an increase in the student activity category from cycle I to cycle II, with an increase of 1.6. Teacher activities in teaching are included in the relatively good category. It is proven from the observations made by obtaining a score in cycle I, namely 9. In cycle II, the score obtained was 14, with an increase of 5. It shows an increase from cycle I, where teacher activities were included in the relatively good to excellent category. This research concludes that the Circuit Learning Strategy can improve student learning outcomes in Class VII Science Subjects at SMPN 4 Mataram in 2022-2023.